Enchantment - Card, Orson Scott (New York : Del Rey/Ballantine, 2000)
American graduate student Ivan Smetski, haunted by the vision of a sleeping princess he believes he saw as a ten-year-old boy while exploring the Carpathian forest, returns to his native land to investigate and, with one kiss, is drawn into a world that vanished a thousand years earlier.
School Library Journal
Wilson's Fiction
Wilson's Senior High School
Adult.
Adult
Keywords: Jews -- Russia -- Fiction; Princesses -- Russia -- Fiction; Sleeping Beauty (Tale) -- Adaptations; Time travel -- Fiction; Jews -- Russia -- Fiction; Princesses -- Russia -- Fiction; Sleeping Beauty (Tale) -- Adaptations; Time travel -- Fiction; Fantastic fiction